PRACTICAL EXAMPLE OF PURCHASING PROCESSES - Borodavkó, Beáta; Bányai Tóth, Ágota; Illés, Béla (Advanced Logistic Systems - Theory and Practice, 2018)
The last century brought significant changes to the automotive industry and represents a significant economic and technological force in the life of countries connected to the industry. The automobile manufacturing fabricates its products primarily through mass production, however, the segment producing exclusive vehicles executes manufacture type production many times due to the small-scale volume. These effects highly impact the international supply chains.